(untitled) (Journal of Social Sciences Review, 2023)
The researchers aimed to explore the practices of prospective teachers regarding peace education in teacher education programs in Punjab, Pakistan. A total of 500 prospective teachers from five public sector universities in Punjab, Pakistan were the population size while the sample respondents were 200 prospective teachers including 100 male and 100 female prospective teachers. The survey method was used to collect the data through a self-developed questionnaire based on 13 themes using a simple random sampling technique. The validity of the tool was properly ensured through experts’ opinions and the instrument was also refined two times in the light of opinions received from experts. The reliability of Cronbach’s Alpha value was found .88. The collected data was organized properly in the form of tables. Both descriptive and inferential statistics were applied to analyze the data such as frequency, mean score difference, standard deviation, percentage, t-value and p-value. The research concluded that the majority of the prospective teachers were hopeful about the practices of peace education but peace education is not presented in the curriculum of teacher education programs. Moreover, the male teachers’ awareness was more as compared to female teachers.